2013
DOI: 10.1007/s10152-013-0368-x
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity gradient in the Baltic Sea: a comprehensive inventory of macrozoobenthos data

Abstract: In the Helsinki Commission Red List project 2009-2012, taxonomic and distributional data of benthic (macro) invertebrates were compiled by the present authors in a comprehensive checklist of the Baltic Sea fauna. Based on the most recent and comprehensive data, this paper presents the diversity patterns observed among benthic invertebrates in the Baltic Sea. As expected, the total number of species per sub-region generally declined along the salinity gradient from the Danish Straits to the northern Baltic Sea.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 8 publications
8
37
0
Order By: Relevance
“…Salinity is considered the key factor for community changes at different spatial scales along the Baltic Sea [6, 10]. Our results confirm that on temporal scales too variability in salinity is an important driver for variation in the benthic community.…”
Section: Discussionsupporting
confidence: 82%
“…Salinity is considered the key factor for community changes at different spatial scales along the Baltic Sea [6, 10]. Our results confirm that on temporal scales too variability in salinity is an important driver for variation in the benthic community.…”
Section: Discussionsupporting
confidence: 82%
“…Similar correlation between the salinity and the species richness and abundance of encrusting assemblages was noted for other taxonomic and functional groups (e.g. Darr et al, 2014;Zettler et al, 2014). Among the environmental variables we studied (including temperature, mean rock size, wave exposure or percent coverage by fauna), salinity showed the strongest relationship with the large-scale pattern of encrusting assemblages.…”
Section: Discussionsupporting
confidence: 71%
“…Comparative measurement of biological parameters describing encrusting assemblages inhabiting the Baltic Sea hydrolittoral and littoral zones (such as species richness, abundance, diversity, percentage cover of fauna) indicated the significant role of local dispersal limitations in encrusting species composition and a strong influence of nearby biotopes. Table 2 The results of the analysis of covariance (ANCOVA) testing the effects of salinity and habitat on the basic community parameters (significant 636 differences are highlighted in bold) where habitat was used as a grouping factor while salinity as covariate Over the scale of the entire Baltic Sea, spatial species distribution is controlled mainly by the steep salinity gradient (Herkül et al, 2006;Zettler et al, 2014), which, according to the results of this study, is also observed in our data and matched our predictions. Along the gradient of increasing salinity, the spatial trends in the hydrolittoral zone, including species composition and increased diversity of encrusting assemblages, were found to be similar to those reported for other macrobenthic communities from deeper regions of the Baltic Sea (Bonsdorff & Pearson, 1999;Westerbom et al, 2002) and in particular, as this study clearly indicated, the nearby littoral.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in accordance with the results of our previous study in which only the July data were considered (Herlemann et al, 2011). The absence of a decline in bacterial diversity in the brackish waters of the Baltic Sea contradicts Remane’s criteria of diversity in the Baltic Sea, deduced from benthic invertebrates, which included a species minimum in the brackish zone (Remane, 1934; Zettler et al, 2014). Deviations from the mesohaline species-minimum proposed for macrozoobenthos have also been noted in other estuaries for bacterial communities (Crump et al, 2004; Hewson and Fuhrman, 2004), zooplankton (Laprise and Dodson, 1994), phytoplankton (Muylaert et al, 2009; Schubert et al, 2011), ciliates (Dolan and Gallegos, 2001), and protists (Telesh et al, 2010).…”
Section: Discussionmentioning
confidence: 77%